Model thresholds are more important than presence location type: Understanding the distribution of lowland tapir (Tapirus terrestris) in a continuous Atlantic forest of southeast Brazil - Norris, Darren (Tropical Conservation Science, 2014)
Modeling the distribution of rare and endangered species is challenging, and there is substantial debate regarding what species distribution models (SDMs) actually represent. Here I investigated whether locations of different lowland tapir signs (feces, trails and tracks) generated different distributions of suitable habitat using a presence-only species distribution modeling technique. Comparison of the equivalence and overlap of the predicted distributions showed no significant differences between the different signs. The contribution of the 11 variables used to build the distribution models was also similar between signs. Although predictions from different signs were similar, the use of different threshold selection methods generated substantially different suitable areas and omission errors. These results highlight the importance of a fundamental understanding of species natural history to determine not only appropriate model parameters, but also the biological relevance of SDMs. My findings also support the need for healthy skepticism regarding what is represented by presence-only species distributions. To help address this skepticism I conclude by providing guidelines for generating reliable local-scale distribution models. © Darren Norris.